Formation Evaluation for Nasiriyah Oil Field Based on The Non-Conventional Techniques - Alhaleem, Ayad A.; Avedisian, Antwan M.; Flayeh, Haider Alwan (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The unconventional techniques called “the quick look techniques”, have been developed to present well log data calculations, so that they may be scanned easily to identify the zones that warrant a more detailed analysis, these techniques have been generated by service companies at the well site which are among the useful, they provide the elements of information needed for making decisions quickly when time is of essence. The techniques used in this paper are:• Apparent resistivity Rwa • Rxo /Rt   The above two methods had been used to evaluate Nasiriyah oil field formations (well-NS-3) to discover the hydrocarbon bearing formations. A computer program had used to represent CPI results for the two mentioned methods, the results of interpretation indicate to hydrocarbon zones in.